The outstanding ability of nanosilica to stabilize dispersions of Nylon 6 droplets in a polypropylene matrix. Issue 22 (27th July 2015) - Sangroniz, Leire; Moncerrate, Marco Antonio; De Amicis, Vladimir A.; Palacios, Jordana K.; Fernández, Mercedes; Santamaria, Antxon; Sánchez, Johan J.; Laoutid, Fouad; Dubois, Philippe; Müller, Alejandro J.
ABSTRACT The effectiveness of hydrophobically modified nanosilica (NS) as interfacial modifying agent for immiscible polymer blends is evaluated. Blends of polypropylene (PP) with 20% of polyamide 6 (PA) and 5% hydrophobic NS were prepared by melt mixing. Compression molded sheets and extruded films were evaluated by scanning electron microscopy, transmission electron microscopy, tensile testing, and rheological measurements. Hydrophobic NS particles strongly reduce the polydispersity and droplet size of the dispersed phase, as a result of their preferential location at the interface. NS promotes outstanding stability of blend dispersion regardless of the processing or post‐processing technique employed. The viscoelastic terminal zone shows a plateau for PP/PA/NS, which corresponds to a suspension‐like behavior. Under large amplitude oscillatory shear, the increment in the non‐linearity parameter Q evidences the interactions between NS and blend components. Therefore, NS is an excellent morphological stabilizer that prevents coalescence, but cannot promote interfacial adhesion between immiscible PP and PA phases. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1567–1579